Multichannel soliton amplification in Erbium-Doped fiber amplifiers - Costa, J. R.; Paiva, C. (Microwave and Optical Technology Letters, 1998)
Soliton amplification in fiber amplifiers has been analyzed using either a parabolic-gain profile (as in the complex Ginzburg-Landau equation) or a Lorentzian profile (as in the set of Maxwell-Bloch equations). For multichannel soliton amplification in erbium-doped fiber amplifiers, we present a new numerical method that takes into account the actual gain profile based on the experimental wavelength dependence of the transition cross sections.